WORKSHOP PENYUSUNAN PROGRAM IMPLEMENTASI TEACHING FACTORY DAN PENYELARASAN KEJURUAN DI SMK NEGERI 1 GUNUNG JATI KABUPATEN CIREBON - Nuri Kartini (Swadaya: Indonesian Journal of Community Empowerment, 2019)
Community Service Activities in the form of a Workshop on Preparation of Teaching Factory Implementation and Vocational Alignment Programs held at SMK Negeri 1 Gunung Jati Cirebon District, Batik and Textile Creative Crafts Expertise Program on Friday, August 9, 2019, has provided meaningful participation for SMKN 1 Gunung Jati, received very good and enthusiastic welcome from the Teaching Factory Team, and DU / DI Batik Cirebon. This can be seen from the participants' enthusiasm when listening to the presentation of material from the speakers, some questions asked by the participants, and very interactive discussions between the speakers and workshop participants. From the results of the discussion and discussion of this activity obtained results, namely 1) Compilation of the mapping of basic competencies of knowledge and skills of batik and textile creative crafts expertise program SMKN 1 Gunung Jati Cirebon Regency for Batik subjects, and 2) Agreement on the alignment of graduate competencies that not only can make products but produce graduates who are ready to become batik entrepreneurs. Keywords: Workshop, Teaching Factory, Batik.